A chemical study of the essential oil of Clausena anisum-olens (Blanco) Merr. (Fam. Rutaceae) - De Jesus, Crisanta R.
A colorless, with a sweetish anise-like odor, essential oil was obtained from the stem and fruit of Clausena anisum-olens (Blanco) Merr. at an average yield of 0.52% and 1.37%, respectively. The fruit oil gave the following physicochemical constants: specific gravity (28°C), 0.9588; refractive index (27°C), 1.5288; specific rotation (27°C), 0.949; acid value, 1.275, and saponification value, 7.63. Due to the small amount of oil obtained from the stem, only refractive index (27°C), 1.5169 was determined. Thin layer chromatographic and ultraviolet spectrophotometric results show that the constituents of both stem oil and fruit oil are almost the sa